Cameroon and Rwanda: A Comparative Analysis of Their Postcolonial Economic Histories. Issue 1 (2nd January 2019) - Prah, Kwesi Dzapong Lwazi Sarkodee
Abstract: This article focuses on the postcolonial economies of Cameroon and Rwanda, two former colonies whose political economies have quintessentially come to define the present character, and nature, of the African state. The social and economic challenges they have faced as sovereign states present serious questions—for both Africans and people worldwide—regarding economic and political development. Are the economies of these states dependent on or independent of their colonial economic heritages? In this regard, are they state-run economies or free-market/mixed-market economies? If they are either of the two types, what has this meant for the states themselves, and how have their political regimes—whether created or inherited—implemented a free-market/mixed-market economy or responded to these economic realities? Through a comparative analysis, utilising primary and secondary sources and data sets, this article argues that the political evolution within these states, and the historical circumstances within which their economies came into being, created economies that have had paradoxical effects. Ultimately, it is argued that historical circumstance, populist politics, and international financial capitalism created neo-colonial economic realities within which Cameroon and Rwanda continue to develop.